(untitled) (Ozone Therapy Global Journal, 2014)
The International Scientific Committee of Ozone Therapy (ISCO3 , http://www.isco3.org) was created in Vienna on October 8, 2010 . One of the first tasks was to create a bank to collect data all possible published research on the topic of ozone therapy. Based on the prev i ous ex perience of t wo researchers it was decided to use the free app Zotero to create the database named " ISCO3 ozone".